Twisters and Traveling Higgs Bosons, Unify General Relativity and Quantum Mechanics, and Explain Dark Matter (Global Journals of Research in Engineering, 2025)
Objective To understand the ultimate functioning of gravity and not to stay on its behavior through formulas and field theories Main theories Loop quantum gravity Strings Twistor Penrose Einstein s Relativity Newton Universal Gravitation etc How to start the research Looking for a common natural phenomenon in our world that produces attraction Tornados and possibility of extending it to atom behavior to understand how this conduct can produce attraction The results obtained are discovery of a reasonable theory of gravity And a surprise this theory Twisters and Traveling Higgs Bosons is able to explain in a logical way Dark Matter mystery Cosmological implications would produce a Quantum Gravity theory